SAR evolution towards potent C-terminal carboxamide peptide inhibitors of Zika virus NS2B-NS3 protease. (1st March 2022) - Colarusso, Stefania; Ferrigno, Federica; Ponzi, Simona; Pavone, Francesca; Conte, Immacolata; Abate, Luigi; Beghetto, Elisa; Missineo, Antonino; Amaudrut, Jerome; Bresciani, Alberto; Paonessa, Giacomo; Tomei, Licia; et al.
Graphical abstract: Abstract: Zika virus (ZIKV) is a member of the Flaviviridae family that can cause neurological disorders and congenital malformations. The NS2B-NS3 viral serine protease is an attractive target for the development of new antiviral agents against ZIKV. We report here a SAR study on a series of substrate-like linear tripeptides that inhibit in a non-covalent manner the NS2B-NS3 protease. Optimization of the residues at positions P 1, P 2, P 3 and of the N -terminal and C-terminal portions of the tripeptide allowed the identification of inhibitors with sub-micromolar potency with phenylglycine as arginine-mimicking group and benzylamide as C-terminal fragment. Further SAR exploration and application of these structural changes to a series of peptides having a 4-substituted phenylglycine residue at the P 1 position led to potent compounds showing double digit nanomolar inhibition of the Zika protease (IC50 = 30 nM) with high selectivity against trypsin-like proteases and the proteases of other flavivirus, such as Dengue 2 virus (DEN2V) and West Nile virus (WNV).